Heat transfer rate and surface pressure measurements in short duration hypersonic flow. (November 2019) - Saiprakash, M.; Kumar, C. Senthil; Sunil, G. Kadam; Rampratap, S.P.; Shanmugam, V.; Balu, G.
ABSTRACT: Experiments were carried out with air as the test gas to obtain the surface convective heating rate and surface pressure distribution on blunt and sharp cone models flying at hypersonic speeds. Tests were performed in a hypersonic shock tunnel at two different angles of attack: 0^° and 5^° with angles of rotation φ = 0^°, 90^°, and 180^° . The experiments were conducted at a stagnation enthalpy of 1.4MJ/kg, flow Mach number of 6.56 and free stream Reynolds number based on the model length of 9.1 × 10^5 . The effective test time of the shock tunnel is 3ms. The results obtained for cone model with a bluntness ratio of 0.2 were compared with sharp cone models for α =0^° . The measured stagnation heat transfer value matched well with the theoretical value predicted by the Fay and Riddell correlation and with the CFD results.